EPUB3 Based Mathematical E-Modules Using the Sigil Application as A Solution in Teaching and Learning Process Through Covid-19 Pandemic - Rahmi Ramadhani; Yulia Fitri (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2021)
This study aim was to develop an EPUB3-based mathematics E-Module using a valid and effective SIGIL application for high school students in Medan, Sumatera Utara. This research is a research and development (R&D) study with the ASSURE model consisting of 6 stages, including analyzing learners-state objectives; select method; media and materials; utilize media and materials; require participant learner; evaluate and revise. The subjects of the study were XI grade senior high school students in Medan, Sumatera Utara, Indonesia. The results showed that the EPUB3-based mathematical E-module was valid and reliable for use in the learning process according to the results of expert validation, with an average value of 3.77 and included in good categories. Furthermore, EPUB3-based Mathematics E-Modules are used in the online learning process, especially in statistical material. Student respondent test results showed that 58% of students felt helped in understanding the material using the EPUB3-based Mathematics E-Modules during online learning. Students more easily learn the material anywhere and anytime and also can test the ability related to statistical material directly on the E-Module to get the final result whether it meets the Minimum Completeness Criteria (KKM) or not. The EPUB3-based Math E-Modules using the SIGIL application is proven to be valid and effective in helping students and teachers carry out online learning during the Covid-19 pandemic.